NIAT BERPINDAH KARYAWAN GENERASI Z DI SITE PERTAMBANGAN PT X : APAKAH KECOCOKAN ORANG-ORGANISASI DAN KEJENUHAN KERJA BERPENGARUH? - Ulfi Laeliatul Ilmi; Wa ode Zusnita Muizu; Ernie Tisnawati Sule (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to examine the relationship between Person-Organization Fit and Turnover Intention, examine the relationship between Job Burnout and Turnover Intention, and describe the role of Job Burnout in mediating the effect of Person-Organization Fit on Turnover Intention. This type of research is quantitative descriptive and verification. The sample amounted to 63 Generation Z employees (aged 18-26 years) of PT X mining site, one of the private mining companies in Indonesia using a closed questionnaire with a Likert Scale. Sampling using non-probability techniques with the total sampling method, and the data was processed and analyzed using SPSS 26 software. Data analysis using hierarchical regression, t-test, and Sobel test. The results showed that (1) Person-Organization Fit has a significant negative effect on Job Burnout; (2) Job Burnout and Turnover Intention have no significant effect but have a positive relationship; (3) There was partial mediation of Job Burnout mediating Person-Organization Fit on Turnover Intention; (4) Person-Organization Fit has a significant negative effect on Turnover Intention.